Radiation Sterilization of Prototype Military Foods. III. Pork Loin - Anellis, Abe (1969)
Ten lots of pork loin, packed in cans, were inoculated with approximately 10(6)Clostridium botulinum spores per can. Each lot was seeded with a different strain; five type A and five type B strains were used. The pack comprised 5,690 cans, including controls, and contained about 10(9) spores per dose. The cans were irradiated with Co(60) in the range of 0 to 5.0 Mrad (0.5 Mrad increments) at 5 to 25 C, incubated for 6 months at 30 C, and examined for swelling, toxicity, and recoverable C. botulinum. The minimal experimental sterilizing dose (ESD) based on nonswollen, nontoxic, but nonsterile end points was 2.5 < ESD ≤ 3.0 Mrad, and based on non-spoiled sterile cans was 3.5 < ESD ≤ 4.0 Mrad. The theoretical minimal radiation dose (MRD), the 12D equivalent, varied with the method of computation: 4.74, 4.33 ± 0.17, and 4.19 to 4.99 Mrad were obtained by the Weibull, Spearman-K̈arber, and Schmidt-Nank techniques, respectively. Calculation of D and MRD values by the conventional Schmidt-Nank method produced increasing values with rising dosage; this finding was compared with the data derived by the other two methods of calculation. Suggestions for estimating the MRD of a prototype radiation process are offered.